Single-Cell RNA sequencing investigation of female-male differences under PAD conditions - Sánchez Marrero, Gloriani; Villa-Roel, Nicolas; Li, Feifei; Park, Christian; Kang, Dong-Won; Hekman, Katherine E.; Jo, Hanjoong; Brewster, Luke P. (Frontiers in Cardiovascular Medicine, 2023)
Peripheral arterial disease (PAD) is an age-related medical condition affecting mostly muscular arteries of the limb. It is the 3rd leading cause of atherosclerotic morbidity. The mechanical environment of endothelial cells (ECs) in PAD is characterized by disturbed blood flow (d-flow) and stiff extracellular matrices. In PAD, the stiffness of arteries is due to decreased elastin function and increased collagen content. These flow and stiffness parameters are largely missing from current models of PAD. It has been previously proven that ECs exposed to d-flow or stiff substrates lead to proatherogenic pathways, but the effect of both, d-flow and stiffness, on EC phenotype has not been fully investigated. In this study, we sought to explore the effect of sex on proatherogenic pathways that could result from exposing endothelial cells to a d-flow and stiff environment. We utilized the scRNA-seq tool to analyze the gene expression of ECs exposed to the different mechanical conditions both in vitro and in vivo. We found that male ECs exposed to different mechanical stimuli presented higher expression of genes related to fibrosis and d-flow in vitro. We validated our findings in vivo by exposing murine carotid arteries to d-flow via partial carotid artery ligation. Since women have delayed onset of arterial stiffening and subsequent PAD, this work may provide a framework for some of the pathways in which biological sex interacts with sex-based differences in PAD.